Propranolol therapy for infantile hemangioma: our experience - Zhang L; Wu HW; Yuan W; Zheng J (Dove Medical Press, 2017)
Ling Zhang,1,* Hai-Wei Wu,1,* Weien Yuan,2 Jia-Wei Zheng1 1Department of Oral-Maxillary Head and Neck, Ninth People’s Hospital, College of Stomatology, Shanghai Jiao Tong University School of Medicine, Shanghai Key Laboratory of Stomatology, Shanghai, 2School of Pharmacy, Shanghai Jiao Tong University, Shanghai, People’s Republic of China *These authors contributed equally to this work Objective: Hemangiomas are the most common benign vascular tumors of infancy. Although most infantile hemangiomas (IHs) have the ability to involute spontaneously after initial proliferation and resolve without consequence, intervention is required in a subset of IHs, which develop complications resulting in ulceration, bleeding, or aesthetic deformity. The primary treatment for this subset of IHs is pharmacological intervention, and propranolol has become the new first-line treatment for complicated hemangiomas. Here, we evaluated the efficacy of propranolol on proliferation IH in a clinical cohort including 578 patients.Methods: We retrospectively reviewed a total of 578 IH patients who were treated with oral propranolol from January 2010 to December 2012. Responses to the propranolol treatment were graded as: excellent, good, poor, or no response. Based on the response to propranolol treatment (once daily at a dose of 1.0 mg/kg for patients younger than 2 months; twice daily at daily total dose of 2 mg/kg for patients older than 2 months), additional pharmacotherapies or surgery were used for IH patients for satisfactory clinical outcome.Results: Five hundred and sixty (96.9%) of 578 IH patients in our study responded to oral propranolol treatment, and the response rate was significantly different for different ages of patients (P<0.05), with the youngest patients having the highest response rate. The mean time of treatment was 6 months (range, 3–12 months). For example, response rate to propranolol was 98.1% in patients younger than 2 months, compared with 93.3% in patients older than 2 months and younger than 8 months, and 73.7% in patients older than 8 months. One hundred and thirty one patients who exhibited incompletely involuted hemangiomas were further treated with timolol maleate (n=89) or pulsed dye laser (n=42). One hundred and seventeen (89.3%) of 131 patients showed a positive response. There were no instances of life-threatening complications after propranolol. However, minor side effects were observed including 10 (1.73%) cases of sleep disturbance, 7 (1.21%) cases of diarrhea, and 5 (0.86%) cases of bronchospasm.Conclusion: IH requires early intervention. During the involution phase, tapering propranolol dosage can be done to minimize side effects before discontinuing treatment. For patients exhibiting telangiectasia and chromatosis after propranolol treatment, administration of a 0.5% solution of timolol maleate or pulse dye laser is an effective therapeutic approach for complete involution. Keywords: propranolol, infantile hemangioma, β-blockers, oral propranolol, intervention studies